2023
DOI: 10.1093/mnras/stad2348
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosynthesis in outflows of compact objects and detection prospects of associated kilonovae

Abstract: We perform a comparative analysis of nucleosynthesis yields from binary neutron star (BNS) mergers, black hole-neutron star (BHNS) mergers, and core-collapse supernovae (CCSNe) with the goal of determining which are the most dominant sources of r-process enrichment observed in stars. We find that BNS and BHNS binaries may eject similar mass distributions of robust r-process nuclei post merger (up to 3rd peak and actinides, A ∼ 200 − 240), after accounting for the volumetric event rates. Magnetorotational (MR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 147 publications
0
6
0
Order By: Relevance
“…In a follow-up work, we will model a longer-lived NS remnant and perform multidimensional kilonova calculations, tracking ejecta from the moment of launch to the kilonova phase. Our work complements ongoing efforts to model populations of kilonovae and determine observing strategies for upcoming surveys such as LSST (Ekanger et al 2023;Setzer et al 2023). Such efforts need to take NS remnant outflows into consideration in order to capture the full spectrum of kilonova transients.…”
Section: Summary and Discussionmentioning
confidence: 89%
“…In a follow-up work, we will model a longer-lived NS remnant and perform multidimensional kilonova calculations, tracking ejecta from the moment of launch to the kilonova phase. Our work complements ongoing efforts to model populations of kilonovae and determine observing strategies for upcoming surveys such as LSST (Ekanger et al 2023;Setzer et al 2023). Such efforts need to take NS remnant outflows into consideration in order to capture the full spectrum of kilonova transients.…”
Section: Summary and Discussionmentioning
confidence: 89%
“…To date, only a few kilonovae have been observed, mainly because of their short lifetimes and relatively low luminosities. However, with the enhancement of follow-up strategies using current telescopes and also with the development of advanced future telescopes like the 7-Dimensional Telescope (Im 2021), the chances of detecting kilonovae are expected to increase significantly (e.g., Cowperthwaite et al 2019;Chase et al 2022;Ekanger et al 2023). In this circumstance, this work proposes a model to explain peculiar kilonova lightcurves that might be observed in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Since the gravitational wave detection from the neutron star merger GW170817 (Abbott et al 2017) and subsequent spectroscopic observations (Watson et al 2019), neutron star mergers are probably the main producers of rprocess elements, as predicted by modern simulations (Thielemann et al 2017). Recently, Ekanger et al 2023 confirmed that black hole-neutron star mergers also produce a significant amount of r-process elements through nucleosynthesis yields from numerical simulations, as indicated by previous studies as well (e.g., Lattimer & Schramm 1976;Freiburghaus et al 1999;Nishimura et al 2016;Kobayashi et al 2023). The r-process also happens at other astrophysical sites, such as core-collapse supernovae (e.g., Wheeler et al 1998;Ekanger et al 2023) and magnetorotational supernovae (e.g., Winteler et al 2012;Reichert et al 2021Reichert et al , 2023.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Ekanger et al 2023 confirmed that black hole-neutron star mergers also produce a significant amount of r-process elements through nucleosynthesis yields from numerical simulations, as indicated by previous studies as well (e.g., Lattimer & Schramm 1976;Freiburghaus et al 1999;Nishimura et al 2016;Kobayashi et al 2023). The r-process also happens at other astrophysical sites, such as core-collapse supernovae (e.g., Wheeler et al 1998;Ekanger et al 2023) and magnetorotational supernovae (e.g., Winteler et al 2012;Reichert et al 2021Reichert et al , 2023. The contribution of core-collapse and magnetorotational supernovae to the abundance of rprocess elements is currently under debate.…”
Section: Introductionmentioning
confidence: 99%